Life Skill Learning Management In Improving Entrepreneurship Student At SMK Negeri South Tangerang - Sunarto, Toto; Wasliman, Iim; Warta, Waska; Tejawiani, Ida (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This research is motivated by the weak life skills and entrepreneurship of Sekolah Menengah Kejuruan (SMK). The purpose of the study was to analyze and describe the management of life skills learning in improving student entrepreneurship at SMK Negeri south Tangerang. This study uses a descriptive method with a qualitative approach through observation, interviews and documentation studies. The theory that underlies this research is the theory of management and learning. The results of the study indicate that: (1) Planning by formulating policies, missions, goals and programs of each school, but has not been supported by educators and the involvement of external school parties. (2) Organizing is arranged according to the program and school resources but has not been supported by teacher resources according to the field of expertise. (3) Actuating in the process is theoretical and practical but not optimal, especially developing student entrepreneurship. (4) Controlling through mentoring and evaluation/assessment by teachers on a regular and scheduled basis but has not been maximized due to lack of resource support and development of areas of expertise. (5) barrier factors include the lack of teachers and teacher entrepreneurship competencies, and the lack of school operational budgets for the development of learning facilities and infrastructure. (6) Solutions: maximizing education staff who have expertise, effectiveness and efficiency of learning time, and are active in competitions in the field of expertise.